Automated Contracting and Pandemic Disruptions: Can Smart Contracts Self-Execute Force Majeure? (Maharaja Surajmal Institute Law Journal, 2026)
Smart contract robots execute blockchain-based contract funding but cannot perform force majeure during a pandemic such as COVID-19 because of hard-coded implementation and unreliable oracles, as occurred when Indian gig platforms automatically imposed lockdown-related penalties on drivers despite some relief in Section 56 Contract Act. This theoretical paper reviews oracle practicability on events such as government lockdown APIs to disclose the risks of manipulation, granularity discontinuities, and empirical disap pointments in supply chain pilots, which necessitated a court intervention in IFAT v Union of India, indicating the imitation of employment by algo rithms. Findings show self-execution demands hybrid models with multi-sig pause buttons, MeitY-certified decentralized oracles, and Indian Contract Act amendments via Section 56A to balance 10 billion dollar blockchain growth with equity for 15 million gig workers under the 2026 Act. Comparative lessons from EU MiCA urge mandatory arbitration, ensuring code efficiency meets judicial nuance for resilient automated contracting in India’s digital economy.
Keywords: Smart contracts, force majeure, self-execution, blockchain, pandemic disruptions, gig workers, hybrid models